Modulation of Life-span by Histone Deacetylase Genes in Saccharomyces cerevisiae - Kim, Sangkyu (The American Society for Cell Biology, 1999)
The yeast Saccharomyces cerevisiae has a limited life-span, which is measured by the number of divisions that individual cells complete. Among the many changes that occur as yeasts age are alterations in chromatin-dependent transcriptional silencing. We have genetically manipulated histone deacetylases to modify chromatin, and we have examined the effect on yeast longevity. Deletion of the histone deacetylase gene RPD3 extended life-span. Its effects on chromatin functional state were evidenced by enhanced silencing at the three known heterochromatic regions of the genome, the silent mating type (HM), subtelomeric, and rDNA loci, which occurred even in the absence of SIR3. Similarly, the effect of the rpd3Δ on life-span did not depend on an intact Sir silencing complex. In fact, deletion of SIR3 itself had little effect on life-span, although it markedly accelerated the increase in cell generation time that is observed during yeast aging. Deletion of HDA1, another histone deacetylase gene, did not result in life-span extension, unless it was combined with deletion of SIR3. The hda1Δ sir3Δ resulted in an increase in silencing, but only at the rDNA locus. Deletion of RPD3 suppressed the loss of silencing in rDNA in a sir2 mutant; however, the silencing did not reach the level found in the rpd3Δ single mutant, and RPD3 deletion did not overcome the life-span shortening seen in the sir2 mutant. Deletion of both RPD3 and HDA1 caused a decrease in life-span, which resulted from a substantial increase in initial mortality of the population. The expression of both of these genes declines with age, providing one possible explanation for the increase in mortality during the life-span. Our results are consistent with the loss of rDNA silencing leading to aging in yeast. The functions of RPD3 and HDA1 do not overlap entirely. RPD3 exerts its effect on chromatin at additional sites in the genome, raising the possibility that events at loci other than rDNA play a role in the aging process.